2015
DOI: 10.1016/j.toxrep.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability assessment of a lectin fraction from Tepary bean seeds ( Phaseolus acutifolius ) orally administered to rats

Abstract: HighlightsWe examine the toxicological profile of Tepary Bean lectins by oral route.Tepary bean lectins showed digestion resistance up to 72 h.Tepary bean lectins induce granulocyte increase after 24 h treatment.A reduction in body weight gain was observed after 6 weeks treatment.No toxicity was observed for Tepary bean lectins after 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…Similar effects were observed with other Tepary bean lectin fractions on different colon cancer cell lines [19,20]. In vivo studies have reported that TBLF (50 mg/kg by intragastric administration for six weeks every third day) exhibits low toxicity, good tolerability and activates the immune system [21,22]. Between the observed adverse effects are loss of body weight, small intestinal villus and colonic crypt atrophy and exocrine pancreas hypertrophy, without systemic adverse effects.…”
Section: Introductionsupporting
confidence: 70%
“…Similar effects were observed with other Tepary bean lectin fractions on different colon cancer cell lines [19,20]. In vivo studies have reported that TBLF (50 mg/kg by intragastric administration for six weeks every third day) exhibits low toxicity, good tolerability and activates the immune system [21,22]. Between the observed adverse effects are loss of body weight, small intestinal villus and colonic crypt atrophy and exocrine pancreas hypertrophy, without systemic adverse effects.…”
Section: Introductionsupporting
confidence: 70%
“…Simulation was run at 100,000 iterations and the final HQs for each NUL dish were recorded. For this particular study, a probable threshold dose (R f D) was assumed, based on a NOAEL of 50 mg /kg-day in animal studies recently reported [28]. In order to use this value as a human safety factor, an uncertainty factor of 10 2 , derived as conversion from animal to man, 10A, and leveraging for all humans, 10H [29] was used to harmonize the dose.…”
Section: Probabilistic Modelling and Data Analysis Of The Exposure Ofmentioning
confidence: 99%
“…TBLF lectins are highly specific in distinguishing between normal and cancer cells; thus, as a consequence, a differential cytotoxic effect is displayed [17] by apoptosis induction and cell cycle arrest [18]. These lectins are particularly resistant and can cross the gastrointestinal tract without being degraded by pH conditions and/or digestive enzymes [19]. Furthermore, TBLF presents low toxicity and inhibits early tumorigenesis in rats with chemically induced colorectal cancer [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These lectins are particularly resistant and can cross the gastrointestinal tract without being degraded by pH conditions and/or digestive enzymes [19]. Furthermore, TBLF presents low toxicity and inhibits early tumorigenesis in rats with chemically induced colorectal cancer [19,20]. When administered intragastrically to rats, TBLF has been shown to have a stimulatory effect on the immune system and displays few side effects, such as atrophy in small intestine villus and colonic crypts and pancreatic hypertrophy, that can be partially reverted after a two-week rest period [21].…”
Section: Introductionmentioning
confidence: 99%